Concentration and purification of infectious bursal disease virus (IBDV) by sucrose density gradient centrifugation - DAS, S C; RAM, G C; VERMA, K C; KATARIA, J M (The Indian Journal of Animal Sciences, 2013)
A protocol to purify infectious bursal disease virus (IBDV) by source density gradient centrifugation was described. IBDV was purified from infected bursa of Fabricious (BF) of chicken by sucrose density gradient centrifugation after fluorocarbon treatment initial and pelleting. Comparison of virus material at different steps of purification by sodium dodecyl sulphate - polyacrylamide gel electrophoresis (SDS-PAGE), absorbance ratio at 260 nm and 280 nm and ELISA showed that the virus gets purified to the maximum extent only after sucrose gradient cenrifugation.